2020
DOI: 10.1021/acsaem.0c01392
|View full text |Cite
|
Sign up to set email alerts
|

In Situ Thermal Runaway Detection in Lithium-Ion Batteries with an Integrated Internal Sensor

Abstract: Thermal safety is of prime importance for any energy-storage system. For lithium-ion batteries (LIBs), numerous safety incidences have been roadblocks on the path toward realizing high-energy-density next-generation batteries. Solutions, viz. electrolyte additives, shut-off separators, and exotic coatings, have limited scope in their operating voltage window, response time, and performance. Various temperature monitoring devices have been tested out with their limitations. Here, we report in situ sensing of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 47 publications
(22 citation statements)
references
References 69 publications
1
21
0
Order By: Relevance
“…The cells opened up around 219 °C for PP compared to 185 °C for CPD-ANF. This may be due to the electrolyte phase change that occurs at T > 80 °C . The peaks for the PP cell appeared more exothermic compared to those for CPD-ANF.…”
Section: Resultsmentioning
confidence: 93%
“…The cells opened up around 219 °C for PP compared to 185 °C for CPD-ANF. This may be due to the electrolyte phase change that occurs at T > 80 °C . The peaks for the PP cell appeared more exothermic compared to those for CPD-ANF.…”
Section: Resultsmentioning
confidence: 93%
“…Also, in LIBs, thermal runaway is typically initiated by exothermic SEI decomposition between 100 and 150 °C. [ 79–85 ] However, previous work using KPF 6 based electrolytes has shown that in KIBs, the SEI actually has a protective effect, shielding intercalated potassium from participating in reactions with the electrolyte, and shifting the onset temperature upward. [ 86 ] Indeed, we find the more robust SEI provided herein by KFSI shifts the exothermic peak upward from 100 to 169 °C for the wetted, potassiated PVDF anode (Figure 8a).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth mentioning as well, that overall heat generation of the charged, wetted KIB anode is less than that of LIBs, with a similar, or even higher onset temperature, suggesting KIBs may be a safer alternative with a rational selection of electrolyte, binder, and cathode. [79][80][81][82][83][84][85]…”
Section: Thermal Safetymentioning
confidence: 99%
“…The measuring capability of the internal RTD depends on its ability to sustain the electrochemical environment of LIBs, which has been shown in our previous work. [ 2,26 ] It has also been shown that temperature gradients exist in the thickness direction of pouch cells. [ 27–29 ] This temperature gradient would be higher for cells with more electrode layers, which creates an opportunity for an internal RTD to detect LIB thermal runaway earlier.…”
Section: Methodsmentioning
confidence: 99%